Disparity of 3 Health Insurance Schemes - Suksamai, Kanitta; Dhebpanya, Pornchai; Sangrugsa, Narin (Journal of Graduate MCU KhonKaen Campus, 2019)
This research aimed to study the context and the problem of disparity of 3 health insurance schemes by using the qualitative research method which was conducted by document analysis and in-depth interviews with the 25key informants related these skills.The research results indicated thattheproblems of disparity in four aspects that found that 1) the budget allocationaspect; both civil servant medical benefit and universal coverage schemereceived 100 percent government budget, unlike the social security scheme people have the right to contribute and the government paid part of it. 2) The schemes management aspect; the payment systems for hospitals were different thataffecting to the quality of medical care and the services provided by the hospitals were different. 3) The health care benefits; it was found that conditions for treatment in the same disease have different treatment conditions, including medicines, supplies, and artificial organs, which differentiate each of the rights for different medical services. And 4) the quality of the medical care and service; it was found that the civil servant medical benefit would be most satisfied, the second was social security scheme, and universal coverage schemerespectively. From these problems, the government should take control of the 3 health insurance schemes to have the same management mechanism, and essential benefits to ensure that people of the 3 health insurance schemes receive equal and fair health services.